Effects of phosphate on the dispersion stability and coagulation/flocculation/sedimentation removal efficiency of anatase nanoparticles. (June 2019) - Liu, Fangyuan; Zhang, Chunpeng; Zhao, Tianrui; Zu, Yilin; Wu, Xuan; Li, Bowen; Xing, Xin; Niu, Jia; Chen, Xiaochen; Qin, Chuanyu
Abstract: This study investigates the behavior and fate of TiO2 NPs in conventional water treatment (coagulation/flocculation/sedimentation) under the influence of waterborne phosphate, focusing on the phosphate uptake rate, surface interactions, and dispersion stability and removal efficiency of TiO2 NPs. The adsorption of HPO4 2− ions on TiO2 NPs (i.e., surface complexation in solution) causes displacement of carbonate species. Moreover, adsorption experiments indicates that complexation of inorganic anions on the surfaces of TiO2 NPs can occur rapidly, within a 5 min time frame. This study confirmed that phosphate would affect the surface charge of the TiO2 NPs; thus, the bridging effect during coagulation may also be hindered by phosphate becoming attached to TiO2 NP surfaces. This information will contribute to nanotechnology-related water safety and water treatment technology. Graphical abstract: Image 1 Highlights: The behavior and fate of anatase NPs in the conventional water treatment process under the influence of waterborne phosphate were investigated. The rate of phosphate uptake by the TiO2 NPs, the interactions on the TiO2 NP surface were clarified. The dispersion stability and removal efficiency of TiO2 NPs was determined quantitatively. The first-hand information is highly expected to contribute to the nanotechnology-related water safety and water treatment technology.